2007
DOI: 10.1186/1743-422x-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The study was carried out to investigate the effects of inoculating three cowpea cultivars: "OLO II", "OLOYIN" and IT86D-719 with three unrelated viruses: Cowpea aphid-borne mosaic virus (CABMV), genus Potyvirus, Cowpea mottle virus (CMeV), genus Carmovirus and Southern bean mosaic virus (SBMV), genus Sobemovirus singly and in mixture on growth and yield of cultivars at 10 and 30 days after planting (DAP). Generally, the growth and yield of the buffer inoculated control plants were significantly higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 12 publications
4
20
0
1
Order By: Relevance
“…The CABMV resistant genotypes proclaimed in the present study could therefore be utilized to develop resistance against multiple viral infections. It is also accounted that early infection of virus severely impedes the crop productivity (Kareem and Taiwo, 2007). The near to 50% reduction in chlorophyll content of infected leaves vis-à-vis healthy plants in the present study could also attribute to severe reduction in yield of infected plants owing to reduced photosynthetic efficiency.…”
Section: Asianmentioning
confidence: 53%
See 1 more Smart Citation
“…The CABMV resistant genotypes proclaimed in the present study could therefore be utilized to develop resistance against multiple viral infections. It is also accounted that early infection of virus severely impedes the crop productivity (Kareem and Taiwo, 2007). The near to 50% reduction in chlorophyll content of infected leaves vis-à-vis healthy plants in the present study could also attribute to severe reduction in yield of infected plants owing to reduced photosynthetic efficiency.…”
Section: Asianmentioning
confidence: 53%
“…As a result, selection of cowpea cultivars with multiple resistances is fundamental to control mixed infections (Anderson et al, 1996). Alternatively, it has been reported that under mixed infections, when symptoms are severe, one of the infecting virus generally is a Potyvirus (Kareem and Taiwo, 2007). Therefore, breeders should use cowpea genotypes with high resistance to viruses from the genus Potyvirus in the production of cowpea cultivars resistant to mixed infection (Lima et al, 2011).…”
Section: Asianmentioning
confidence: 99%
“…(2 n = 22), is one of the most ancient human food sources [1]. It is one of the most important legume crops in the world and it is a major food crop in Africa, Latin America, and India because of its high protein content [2, 3]. As a result, cowpea is referred to as a poor man's meat [4].…”
Section: Introductionmentioning
confidence: 99%
“…The main viruses reported globally on the plant include Cowpea mild mottle virus (CPPMV, carlavirus), Voandzeia mosaic necrosis virus (VMNV, tymovirus), Cowpea mottle virus (CPMoV, carmovirus), Southern bean mosaic virus (SBMV, sobemovirus), Cucumber mosaic virus (CuMV, cucumovirus) as well as a number of potyviruses, namely Cowpea aphid aphid-borne mosaic virus (CABMV), Bean common mosaic virus blackeye strain (BCMV-BlCM), Voandzeia distortion mosaic virus (VDMV), Peanut mottle potyvirus (PnMV) [3] [4]. Viruses of genus Potyvirus are major factors of the reduction of Bambara groundnut production by causing yield losses ranging between 13% and 100% in cowpea [5] [6]. Potyviruses are mostly transmitted by aphid vectors and through virus contaminated seeds, which makes their control difficult.…”
Section: Introductionmentioning
confidence: 99%